2020
DOI: 10.1016/j.chemosphere.2020.126919
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-related effects of pentabromophenol, tetrabromobisphenol A, and triphenyl phosphate on murine BV-2 microglia cells

Abstract: The predominant reliance on bromated flame retardants (BFRs) is diminishing with expanded use of alternative organophosphate flame retardants. However, exposure related issues for susceptible populations, the developing, infirmed, or aged, remain given environmental persistence and home environment detection. In this regard, reports of flame retardant (FR)-related effects on the innate immune system suggest process by which a spectrum of adverse health effects could manifest across the life-span. As representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 100 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…While the function of the NLRP3 inflammasome in astrocytes is controversial, it is known to be expressed and activated in microglia (Gustin et al, 2015;Freeman and Guo, 2017;Slowik et al, 2018). Evidence shows that pentabromophenol (PBP) and tetrabromobisphenol A (TBBPA) improves the metabolic rate of glycolysis in mouse microglia and promotes the activation of NLRP3 inflammasome (Bowen et al, 2020). Hexokinase is one of the key glycolytic enzymes.…”
Section: Glycolysis Dysfunction Normal Mechanism and Biological Functionmentioning
confidence: 99%
“…While the function of the NLRP3 inflammasome in astrocytes is controversial, it is known to be expressed and activated in microglia (Gustin et al, 2015;Freeman and Guo, 2017;Slowik et al, 2018). Evidence shows that pentabromophenol (PBP) and tetrabromobisphenol A (TBBPA) improves the metabolic rate of glycolysis in mouse microglia and promotes the activation of NLRP3 inflammasome (Bowen et al, 2020). Hexokinase is one of the key glycolytic enzymes.…”
Section: Glycolysis Dysfunction Normal Mechanism and Biological Functionmentioning
confidence: 99%
“…This agrees with our results, in which 1 μM TCS did not change β-cell viability. Despite the lack of evidence in pancreatic β-cells, it has been shown that exposure to high doses of TPP and DDE (>10 μM) induced apoptosis in other cells and tissues: TPP in hepatocytes, epithelial tumoral JEG-3 cells from placenta, and murine BV-2 microglia [5355]; and DDE in Sertoli cells [56,57]. Exposure to high concentrations of p,p’ -DDT (>150 μM) for 24 h decreased viability in NES2Y human pancreatic β-cell line [58].…”
Section: Discussionmentioning
confidence: 99%
“…Microglia also exploit glycolysis to maintain the immune functional response [ 23 ]. In particular, enhancing glycolytic flux in the microglia promotes inflammasome activation [ 24 ]. Glucose 6-phosphate (G6P) can be channeled into the pentose phosphate pathway (PPP) [ 25 ], which promotes the two-step oxidative decarboxylation of G6P catalyzed by glucose-6-phosphate dehydrogenase (G6PD) and 6-phosphogluconate dehydrogenase (6PGD), yielding ribulose-5-phosphate (R5P).…”
Section: Brain Metabolism In Physiological Conditionsmentioning
confidence: 99%